The therapeutic potential of etoricoxib in clinical practice - A. E. Karateev (Современная ревматология)
Etoricoxib is one of the most popular representatives of a group of nonsteroidal anti-inflammatory drugs (NSAIDs), which is widely used in Russia and other countries of the world. It is a highly selective cyclooxygenase 2 inhibitor that has a rapid and pronounced analgesic effect, a high antiinflammatory potential, and an ability to affect the development of central sensitization, one of the central mechanisms for chronic pain. The therapeutic potential and safety of etoricoxib have been extensively tested in numerous large-scale randomized controlled trials (RCTs). It has proven to be an effective agent for relief of acute pain (including that in dental practice) and acute gouty arthritis, for long-term treatment of rheumatoid arthritis, ankylosing spondylitis (AS), and osteoarthritis (OA). A meta-analysis of a series of RCTs suggests that etoricoxib may be a more effective analgesic drug for AS and OA than other NSAIDs. Etoricoxib significantly less frequently cause gastrointestinal complications than non-selective NSAIDs. The cardiovascular risk associated with etoricoxib is not higher than that with non-selective NSAIDs such as diclofenac.